2019
DOI: 10.1371/journal.pone.0221248
|View full text |Cite
|
Sign up to set email alerts
|

The combination of ACE I/D and ACE2 G8790A polymorphisms revels susceptibility to hypertension: A genetic association study in Brazilian patients

Abstract: Background Systemic arterial hypertension (SAH) is a multifactorial condition that already affects one third of the worldwide population. The identification of candidate genes for hypertension is a challenge for the next years. Nevertheless, the small contribution of each individual genetic factor to the disease brings the necessity of evaluate genes in an integrative manner and taking into consideration the physiological interaction of functions. Angiotensin I–converting enzymes, ACE and ACE2, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 48 publications
4
93
0
3
Order By: Relevance
“…Uemura et al [10] observed a statistically significant association of the D allele and high systolic and diastolic blood pressure in the Japanese population and obesity, hyperlipidemia, hypertension, and diabetes mellitus more prevalent among the ID and DD genotypes, compared to the II genotype. In another study involving a Brazilian population, no direct association of I/D polymorphism of the ACE gene and G8790A polymorphism of the ACE2 gene and systemic arterial hypertension was observed although significant association of the combination of the DD genotype and GG genotype with systemic arterial hypertension was observed [11]. A study in southeast Turkey indicated that women with DD or ID genotypes had a 72% increased risk of idiopathic recurrent pregnancy loss [12], while another study in northern Iran found the DD genotype to be more prevalent among women who have experienced recurrent pregnancy loss [13].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Uemura et al [10] observed a statistically significant association of the D allele and high systolic and diastolic blood pressure in the Japanese population and obesity, hyperlipidemia, hypertension, and diabetes mellitus more prevalent among the ID and DD genotypes, compared to the II genotype. In another study involving a Brazilian population, no direct association of I/D polymorphism of the ACE gene and G8790A polymorphism of the ACE2 gene and systemic arterial hypertension was observed although significant association of the combination of the DD genotype and GG genotype with systemic arterial hypertension was observed [11]. A study in southeast Turkey indicated that women with DD or ID genotypes had a 72% increased risk of idiopathic recurrent pregnancy loss [12], while another study in northern Iran found the DD genotype to be more prevalent among women who have experienced recurrent pregnancy loss [13].…”
Section: Introductionmentioning
confidence: 89%
“…Given that ACE plays a key role in the renin-angiotensin system that regulates fluid volume and controls blood pressure, it is highly likely that I/D polymorphism of the ACE gene could have diverse physiological consequences. Indeed, the I and D alleles of the ACE gene have been associated with an increased risk for many diseases [7][8][9][10][11][12]. Uemura et al [10] observed a statistically significant association of the D allele and high systolic and diastolic blood pressure in the Japanese population and obesity, hyperlipidemia, hypertension, and diabetes mellitus more prevalent among the ID and DD genotypes, compared to the II genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, these effects are being investigated in ongoing clinical trials (ClinicalTrials.gov NCT04287686), alongside the use of losartan as first therapy for COVID-19 in hospitalized (NCT04312009) or not hospitalized patients (NCT04311177). A major role in the pathogenesis of (as well as in the clinical response to) COVID-19 could also be played by ACE2 polymorphisms, which are relatively under-investigated if compared to ACE [129,130].…”
Section: Ace2 and Anti-hypertensive Drugs: What Do We Know?mentioning
confidence: 99%
“…The ACE2 gene (which is located on X chromosome) is characterized by a large polymorphism, and significant associations between polymorphisms and occurrence of arterial hypertension have been reported for women of different race and ethnicity and in Han Chinese men [10][11]. More recently, the combination of ACE1 and ACE2 polymorphisms has been associated with susceptibility to hypertension in Brazilian patients [12]. Within the Chinese population, the polymorphism distribution seems different between regions; polymorphisms of ACE2 are associated with different blood pressure response to the cold pressor test.…”
Section: The Co-protagonistsmentioning
confidence: 99%